Analisis Pengungkapan Kinerja Ekonomi Berdasarkan Standar Gri 200 Pada Perusahaan Sektor Healthcare Di Bursa Efek Indonesia - Indah sukma ningsih rangkuti; Difa putri ayu syakina (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the level of economic performance disclosure based on the Global Reporting Initiative (GRI) 200 Standards among healthcare sector companies listed on the Indonesia Stock Exchange (IDX). The study employs a descriptive approach using content analysis of sustainability reports and/or annual reports of healthcare companies for the year 2024, by assessing the extent of disclosure against GRI 200 indicators and the adoption of the latest GRI standards. The results indicate that sustainability reporting practices in the healthcare sector remain limited, with only 11% of companies publishing sustainability reports, while 89% have not issued such reports. Economic performance disclosure based on GRI 200 is also very low, as only 4% of companies disclose information in accordance with the standards, 3% disclose information that is not compliant, and 93% do not disclose GRI 200 at all. In addition, only 13% of companies have adopted the GRI 2021 Standards, while 87% have not yet implemented them. These findings highlight a significant gap between the publication of sustainability reports and the quality of economic performance disclosure, emphasizing the need for stronger corporate commitment and regulatory support to enhance transparency and compliance with GRI Standards.